A cross sectional study on prescribing pattern for children at primary health care clinics - Jorige, Archana; B., Lohitha; S. L., Lavanya (International Journal Of Community Medicine And Public Health, 2020)
Background: Rational prescribing for pediatrics is very essential as there is increased risk from the use of medicines in them due to multiple reasons ranging from altered pharmacokinetics to long-term side effects. Drug related needs of children must be assessed on individual basis to meet appropriate health care out comes. This cross-sectional descriptive study aimed at assessing drug use pattern and rationality in prescribing pattern as per World Health Organization (WHO) core prescribing indicators. Methods: A cross-sectional and prospective study was carried out in private primary health care clinics of Hyderabad, Telangana State. A total number of 300 prescriptions for children were reviewed. Patients’ demographic characters, diagnosis, and drugs prescribed were recorded in a pre-structured and validated data collection form. Results: Average number of drugs per prescription is 1.92. Fever and upper respiratory tract infections were found to be common complaints in this age group. Paracetamol is the mostly prescribed medication and among prescribed antibiotics, Fluroquinolones occupied major part. 67.3% of drugs were from the WHO model list of essential medicines for children. The percentage of drugs prescribed with generic names is very less. Conclusions: In this study it was found that the prescription pattern in the selected primary healthcare centers in Hyderabad was in compliance with the WHO prescribing indicators except the generic prescribing practice.